Three essays on the economics of preferential trade agreements: free trade areas, rules of origin and customs unions - Xiao, Renfeng (Kansas State University, 2010)
There have been considerable discussions about why countries have interests in forming preferential trade agreements (PTAs), which typically take the forms of a “free trade area” (FTA) with Rules of Origin (ROO) and a “customs union” (CU) (World Bank, 2005). This dissertation contains three essays with three different models of trade under oligopoly to analyze various issues on preferential trade agreements. The first essay examines welfare implications of forming preferential trade arrangement (PTAs) between two asymmetric countries that differ in their market sizes. Key findings are as follows. First, when market size asymmetry between two countries is not too large and ROO requirements are not too restrictive, the formation of an FTA with effective ROO can be welfare-improving to both members. Second, the formation of a PTA is more likely to emerge between countries of similar in their market sizes, ceteris paribus. Third, compared to the pre-PTA equilibrium, there are greater reductions in external tariffs under an FTA than under a CU such that a non-member country is relatively better off under the FTA. The second essay presents a three country model of trade under Bertrand price competition to analyze differences in welfare implications between an FTA with ROO and a customs union (CU). It is shown that the maximum limit of ROO requirements over which there are welfare gains from trade for FTA members depends crucially on the degree of substitutability of final goods (or the intensity of product market competition). It is also found that member countries and their final-good exporters are better off in a CU than in an FTA. There are greater reductions in external tariffs under an FTA than under a CU such that a non-member country is relatively better off under the FTA. The third essay presents a three country model of FTA with Cournot quantity competition and derives the maximum enforceable level of ROO over which there are welfare gains from trade to each member country. It is shown that ROO and external tariffs are strategic complements such that the higher is the regional input restrictions, the higher is the external tariff necessary to induce firms to fully comply with ROO requirements. It is also shown that an FTA with effective ROO has a positive effect on the final-good trade. But the trade-diverting effect does not occur in the final-good sector.
Keywords: Customs union; Free trade area; Rules of origin; Preferential trade agreements; welfare; Economics, Theory (0511)